Psycho-Socio Analysis of Shashi Deshpande’s the Dark Holds No Terrors: An examination of societal pressure and gender dynamics in Shashi Deshpande's The Dark Holds No Terrors (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Marriage is the destiny of the woman to remain unmarried is suggestive of unnaturalness. It brings shame to the woman’s family. It is the parents’ social obligation and moral responsibility to get their daughter married before she passes the marriageable age. For the sake of social approval and her parent’s happiness, the girl has to go through the humiliating ‘inspection’ where she is examined by the boy’s relatives as if she is a saleable commodity. Denied the freedom to choose or express herself, she is forced into marriage rituals. Neither her parents nor the man ask what she wants. Deshpande’s concern with the patriarchal concept that a woman must exist only in terms of her relationship with a man where he will be able to control all stages of her life.